1985
DOI: 10.1080/02786828508959056
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Humidity on Fine-Particle Aerosol Dynamics and Precipitation Scavenging

Abstract: Precipitation chemistry and the chemical composition and mass loading of atmospheric fine-particle aerosols were examined for 25 individual precipitation events during a 12-month period. Aerosol and precipitation data were used (a) to determine the influence of the precipitation event on the mass loading and the chemical composition of the fine-particle aerosol, and (b) to calculate the apparent scavenging ratios for sulfate and ammonium ions. Two distinct types of aerosol behavior were observed. In one, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The increase in PM 2.5 during rainy periods may be attributed to an increase in RH. One study [22] found that for particles with an aerodynamic diameter between 0.3 and 1.0 µm, RH can affect the particles' mass more strongly than precipitation, potentially increasing their mass concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in PM 2.5 during rainy periods may be attributed to an increase in RH. One study [22] found that for particles with an aerodynamic diameter between 0.3 and 1.0 µm, RH can affect the particles' mass more strongly than precipitation, potentially increasing their mass concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Southeast Asia (Ma et al, 2003) showed that the biomass burning plume contributes approximately 35-40% of the fine organic aerosol mass in the Pacific Ocean. The concentration of aerosol particle were observed to decrease during rain (Sisterson et al, 1985) The studies conducted in Gaborone, Botswana (Jayaratna and Verma and Thomas, 2007) also showed that there is an increase in atmospheric particle concentration during winter season due to biomass burning.…”
Section: Introductionmentioning
confidence: 95%